MENGUKUR KINERJA KEUANGAN DENGAN PENDEKATAN ECONOMIC VALUE ADDED - Saripah - Saripah (JABE (Journal of Applied Business and Economic), 2020)
This study aims to determine how the financial performance of the computer services and equipment subsector companies with the economic value added. The population of this research is all of the computer services and equipment subsector companies listed on the Indonesia stock exchange. Sampling from this study is through purposive sampling technique obtained 6 companies as a sample. Economic value-added analysis techniques are used in this research. The results of this study from 6 research samples 5 companies have a positive economic value added in 2017 while1 company has a negative economic value-added, it’s similar in 2018 there is 5 positive economic value added result and 1 negative economic value added. The difference in 2018 is that the number of economic value added for each company that has positive results is greater than in 2017. The cause of the differences in 2017 and 2918 is an increase in EBIT and NOPAT and a decrease in taxes and WACC.